Feeling happy and carefree: a qualitative study on the experiences of parents, medical clowns and healthcare professionals with medical clowns - Jesminne Bruins Slot; Michelle Hendriks; Ronald Batenburg (International Journal of Qualitative Studies on Health & Well-Being)
Purpose: To explore the effect of medical clowns and its relevant actors and conditions. Method: Semi-structured interviews were conducted with fourteen parents who had experiences with medical clowns in the Netherlands. Four focus groups were held with seven medical clowns and 25 healthcare professionals. The interviews and focus groups were audio-recorded and transcribed verbatim. Content analysis was used to analyse the data. Results: Concerning the clown effect, we distinguished the following themes: happiness, distraction, carefree feeling and activation. This effect depended upon clown characteristics (appearance, tailoring, low-key play, making an effort); child characteristics (age, autonomy, fear, living cut off from society, communication); parent characteristics (autonomy, attitude); healthcare professional characteristics (attitude, communication); and organizational conditions (timing and planning, collaboration, accessibility, awareness). Conclusion: This study shows that medical clowns are of value for children with serious illnesses or mental disabilities in several care settings. An asset of medical clowns is that they tailor their play to the child and situation.Support of and communication with parents and healthcare professionals is critical. The proposed model of the clown effect can help shape future research. The results can help medical clown organizations to enhance their services and optimize clown encounters.